PENGARUH KEMITRAAN KOPERASI MANDIRI JAYA TERHADAP PENDAPATAN ANGGOTA PADA PT PATIWARE KABUPATEN BENGKAYANG - Amanda, Yuga; Rustiyarso, Rustiyarso; Khosmas, F.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem in this research is "Is There Effect of Mandiri Jaya Cooperative Partnership on Member Income Rate at PT Patiware Oil Palm Plantation in Â Distric of Sungai Raya Kepulauan Bengkayang Regency". The method used in this research is descriptive method with form of study relationship with population 100 people and a sample of 80 people. Data collection techniques used are direct communication techniques, indirect communication techniques, and document study techniques. Meanwhile, to analyze the data of researchers using computerized SPSS version 16 and Ms Excel 2010. Based on the research data obtained, it is stated there is influence between partnership of independent cooperative victorious against the level of income members at PT Patiware oil palm plantations in Distric Sungai Raya Bengkayang Regency with coefficient value correlation of 0.516 at the intermediate relationship interpretation level. then the value of R Square 0,266 is determined by the formula KD = R ^ 2 x 100% (KD = 0,266 x 100%) to 26,6%, meaning that influence from partnership of independent cooperative to member income equal to 26,6% and the rest influenced by factors outside the researcher. Keywords: Cooperative Partnership, Oil Palm, Member's RevenueÂ